Mutations of Oncoprotein 18/Stathmin Identify Tubulin-Directed Regulatory Activities Distinct from Tubulin Association - Larsson, Niklas (American Society for Microbiology, 1999)
Oncoprotein 18/stathmin (Op18) is a recently identified phosphorylation-responsive regulator of the microtubule (MT) system. It was originally proposed that Op18 specifically regulates dynamic properties of MTs by associating with tubulin, but it has subsequently been proposed that Op18 acts simply by sequestering of tubulin heterodimers. We have dissected the mechanistic action of Op18 by generation of two distinct classes of mutants. One class has interruptions of the heptad repeats of a potential coiled-coil region of Op18, and the other involves substitution at all four phosphorylation sites with negatively charged Glu residues. Both types of mutation result in Op18 proteins with a limited decrease in tubulin complex formation. However, the MT-destabilizing activities of the coiled-coil mutants are more severely reduced in transfected leukemia cells than those of the Glu-substituted Op18 derivative, providing evidence for tubulin-directed regulatory activities distinct from tubulin complex formation. Analysis of Op18-mediated regulation of tubulin GTPase activity and taxol-promoted tubulin polymerization showed that while wild-type and Glu-substituted Op18 derivatives are active, the coiled-coil mutants are essentially inactive. This suggests that Op18-tubulin contact involves structural motifs that deliver a signal of regulatory importance to the MT system.